High Modulation Speed, Depth, and Coloration Efficiency of Carbon Nanotube Thin Film Electrochromic Device Achieved by Counter Electrode Impedance Matching. Issue 20 (8th August 2018) - Stekovic, Dejan; Arkook, Bassim; Li, Guanghui; Li, Wangxiang; Bekyarova, Elena; Itkis, Mikhail E.
Abstract: Improving the modulation depth and switching speed of electrochromic devices is important for expanding the field of electrochromic functional materials applications. The previous study demonstrates that semiconducting (SC‐) single‐wall carbon nanotube (SWNT) thin film based electrochromic cells with ionic liquid as the electrolyte and metallic (MT‐) SWNT counter electrode can operate with fast switching times in the millisecond range. However, achieving a high modulation depth requires an increasing thickness of the electrochromically active SC‐SWNT layer resulting in a slowdown of the switching time by more than order of magnitude. Here it is reported that milliseconds range switching time can be restored by increasing the thickness of MT‐SWNT thin film counter electrode thus matching the electrochemical capacitances of the two sides of the electrochromic cell while reaching a high modulation depth of 20 dB and high coloration efficiency exceeding 1800 cm 2 C −1 at an infrared wavelength of 1770 nm. The results are interpreted in terms of considering the SWNT cell as a supercapacitor with two connected in series electric double layer 3D capacitors associated with two opposing SWNT electrodes. Abstract : Fast operation of single‐wall carbon nano‐tube (SWNT) electrochromic device is achieved for high thicknesses of electrochromically active semiconducting SWNT films by increasing thickness of metallic SWNT counter electrode to match electrochemical capacitances of both electrodes. The balanced device shows modulation depth of 20 dB, millisecond range response time, and coloration efficiency exceeding 1800 cm 2 C −1 at infrared wavelength 1770 nm.